THE CULTURE OF MARRIAGE IN FAMILY RELATIONS (Symposium on Natural and Applied Sciences, 2026)
This article examines the culture of marriage within the framework of family relations, highlighting its significance as a matter of state importance for nurturing future generations. Drawing on the etymological roots of 'nikah' as a sacred union, the author explores the foundational role of the family as the primary nucleus of society. The study defines marital culture through its physiological, ethical, and legal dimensions, emphasizing that a successful marriage requires both physical health and spiritual maturity.The source identifies several contemporary challenges, including the negative influence of "popular culture" on youth, the risks associated with virtual courtship, and the critical issue of consanguineous marriages, which significantly increase the risk of genetic disorders. Furthermore, the article underscores the importance of legal literacy and mutual respect between spouses to prevent domestic abuse. Ultimately, the author concludes that stable family relations, anchored in discipline and respect for rights, are essential for the prosperity of the nation and the state.
Keywords: Marriage culture, family relations, nikah, matchmaking, consanguineous marriage, genetic disorders, ethical education, youth, legal protection, Uzbekistan.